IMPLEMENTATION OF E-PROCUREMENT POLICY AS A REALIZATION OF GOOD GOVERNANCE IN THE GOODS AND SERVICES PROCUREMENT BUREAU OF WEST KALIMANTAN PROVINCE - Dithya Sri Puji Rizqi; Sri Haryaningsih; Ida Rochmawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study uses a qualitative descriptive approach aimed at examining the implementation of electronic procurement of goods and services (e-Procurement) policies at the Procurement Bureau of Goods and Services of West Kalimantan Province. The background of the study is based on the need to modernize the procurement system to improve efficiency, transparency, and accountability in budget management. Primary data were obtained through in-depth interviews and observations, while secondary data came from documentation studies. The analysis was conducted using Charles O. Jones's policy implementation theory, which includes organizational dimensions, interpretation, and application, and is linked to the principles of good governance, including transparency, participation, accountability, and governance effectiveness. The results show that organizationally, the implementing structure has been established, but there is still a lack of certified procurement human resources. From an interpretation perspective, limited training and socialization create a gap in technical understanding. In terms of application, the e-Procurement mechanism runs according to procedure, but faces obstacles such as system disruptions, limited integration between platforms, and suboptimal readiness of small and medium enterprises. This study recommends institutional strengthening, equitable distribution of human resource training, and the development of reliable information technology infrastructure to support the effective implementation of e-Procurement in line with the principles of good governance.